Improving of Creative Thinking Skill through Coding for all at Elementary Students - Saptajiah, Intan Saptajiah; Slameto, Slameto (Kirana Publisher (KNPub), 2024)
This study explores the influence of coding for all on enhancing creative thinking skills among elementary students. 21st Century skills are essential abilities that help people work well with others, think of new ideas, speak clearly, and solve problems in this era world. It focuses in particular on the key soft skills competencies known as the